2015
DOI: 10.1007/s10886-015-0597-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory Increases Fruit Set in Silene latifolia: A Consequence of Induced Pollinator-Attracting Floral Volatiles?

Abstract: Although the effect of herbivory on plant reproduction has been investigated in some detail, little is known about how herbivores affect floral signalling. Here, we investigated the effect of foliar herbivory by the African Cotton Leafworm (Spodoptera littoralis) on floral signalling and fruit set in the White Campion (Silene latifolia). We found no effects of herbivory on floral traits involved in visual signalling (flower number, corolla diameter, calyx length, petal length) or in amount of nectar produced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Still, some flower traits seem to be more plastic than others and may contribute more to pollinator attraction, more so when the trait provides information on floral rewards. Especially floral volatiles seem to undergo profound changes in response to herbivory (Cozzolino et al, 2015;Kessler & Halitschke, 2009;Lucas-Barbosa et al, 2016;Pareja et al, 2012;Schiestl et al, 2014) and may explain changes in pollinator behaviour well (Kessler & Halitschke, 2009;Schiestl et al, 2014), although it is often unclear which individual compounds are used by pollinators (but see Knauer & Schiestl, 2015). Other flower traits like colour and morphology also change in response to herbivory and are important for pollinator attraction (Campbell, Bischoff, Lord, & Robertson, 2010;Hempel de Ibarra, Langridge, & Vorobyev, 2015;Strauss, Conner, & Rush, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, some flower traits seem to be more plastic than others and may contribute more to pollinator attraction, more so when the trait provides information on floral rewards. Especially floral volatiles seem to undergo profound changes in response to herbivory (Cozzolino et al, 2015;Kessler & Halitschke, 2009;Lucas-Barbosa et al, 2016;Pareja et al, 2012;Schiestl et al, 2014) and may explain changes in pollinator behaviour well (Kessler & Halitschke, 2009;Schiestl et al, 2014), although it is often unclear which individual compounds are used by pollinators (but see Knauer & Schiestl, 2015). Other flower traits like colour and morphology also change in response to herbivory and are important for pollinator attraction (Campbell, Bischoff, Lord, & Robertson, 2010;Hempel de Ibarra, Langridge, & Vorobyev, 2015;Strauss, Conner, & Rush, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Flower traits are highly plastic and change readily in response to environmental factors, such as herbivory (Lucas-Barbosa, van Loon, & Dicke, 2011;Strauss, 1997). Changes in response to herbivory include most flower traits involved in pollinator attraction (Bruinsma et al, 2014;Cozzolino et al, 2015;Hoffmeister et al, 2016;Lucas-Barbosa et al, 2016). Herbivore-induced changes in floral traits may vary considerably depending on herbivore species (Pareja et al, 2012;Rusman et al, 2018).…”
mentioning
confidence: 99%
“…In Silene (Caryophyllaceae), volatiles released following herbivore attack to leaves increase fruit set via increased pollinator attraction (Cozzolino et al. ).…”
Section: Hypothesis 1: Prezygotic Mechanismsmentioning
confidence: 99%
“…Finally, an evolutionary shift in leaf volatiles could potentially have a direct effect on which pollinator species visit a flower. In Silene (Caryophyllaceae), volatiles released following herbivore attack to leaves increase fruit set via increased pollinator attraction (Cozzolino et al 2015).…”
Section: Pathway 1: Coupled Herbivore Defense and Pollinator Attractionmentioning
confidence: 99%
“…However, whereas herbivory reduces male reproductive success, female reproductive success was not affected by herbivory. In a recent study, Cozzolino et al (2015) showed that Spodoptera-infested S. latifolia female plants had increased fruit production, likely mediated by increased production of pollinator-attracting floral scent compounds. This supports the idea that, in contrast to male plants, the reproductive effort is not yet maximised in female plants (Lloyd, 1980) and can be enhanced upon herbivore attack.…”
Section: Discussionmentioning
confidence: 99%